1999
DOI: 10.1016/s1074-7613(00)80073-4
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor c-Maf Controls the Production of Interleukin-4 but Not Other Th2 Cytokines

Abstract: IL-4 promotes the differentiation of naive CD4+ T cells into IL-4-producing T helper 2 (Th2) cells. Previous work provided suggestive but not conclusive evidence that the transcription factor c-Maf directed the tissue-specific expression of IL-4. It was not known whether c-Maf controlled the transcription of other Th2 cytokine genes. To elucidate the role of c-Maf in vivo, we examined cytokine production in mice lacking c-Maf (c-maf(-/-)). CD4+ T cells and NK T cells from c-maf(-/-) mice were markedly deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
259
3
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 342 publications
(282 citation statements)
references
References 50 publications
19
259
3
1
Order By: Relevance
“…However, IL-4 was blocked, as demonstrated by inhibition of both IL-4 mRNA and serum IgE elevations, when B7 costimulation was abrogated. These studies thus demonstrate differential regulation of IL-4 and IL-13 in T cells by costimulatory molecules during the in vivo immune response, consistent with previous studies indicating that these Th2 cytokines can be differentially regulated by certain transcription factors [10,11]. Our studies further indicate that DX5 + cells are also a major source of IL-13.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, IL-4 was blocked, as demonstrated by inhibition of both IL-4 mRNA and serum IgE elevations, when B7 costimulation was abrogated. These studies thus demonstrate differential regulation of IL-4 and IL-13 in T cells by costimulatory molecules during the in vivo immune response, consistent with previous studies indicating that these Th2 cytokines can be differentially regulated by certain transcription factors [10,11]. Our studies further indicate that DX5 + cells are also a major source of IL-13.…”
Section: Discussionsupporting
confidence: 91%
“…However, other studies suggest that under certain circumstances IL-4 and IL-13 are regulated independently, and certain signaling pathways involving c-maf [10] and GATA-3 [11] can differentially regulate these two cytokines. Consistent with these findings, several in vivo studies have recently identified IL-4-independent elevations of IL-13 associated with an IFN-c-dominant response [8,12], although the cell surface or secreted molecules that induce the development of IL-13-expressing cells in this context remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Several developmentally regulated transcription factors, such as GATA-3 and c-maf, have been shown to be critical for the generation of IL-4 producing Th2 cells (Ho et al, 1996;Kim et al, 1999;Zheng and Flavell, 1997). The expression of these transcription factors is induced as Th precursor cells become Th2 e ectors.…”
Section: Stat6 and T Helper Cell Differentiationmentioning
confidence: 99%
“…Furthermore, c-maf -/-mice showed greatly impaired IL-4 production, and their T cells spontaneously polarized towards a Th1 phenotype. However, under Th2-differentiating conditions, c-Maf-deficient Th2 cells produced normal amounts of Th2 cytokines, indicating that c-Maf is not required for chromatin remodeling at the IL-4/IL-13 locus but rather specifically regulates IL-4 gene expression in peripheral T lymphocytes [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…c-Maf is a transcription factor of the maf gene family expressed in Th2 but not Th1 cells [15] that is responsible for tissue-specific expression of the IL-4 gene [15][16][17]. The maf gene family includes the large maf genes (c-maf, mafB and Nrl) and the small maf genes (mafK, mafG and mafF), which lack the N-terminal half of the large maf genes containing the transactivation domain [18].…”
Section: Introductionmentioning
confidence: 99%